An organolanthanide(iii) single-molecule magnet with an axial crystal-field: influence of the Raman process over the slow relaxation. Issue 34 (12th April 2017) - Long, Jérôme; Shestakov, Boris G.; Liu, Dan; Chibotaru, Liviu F.; Guari, Yannick; Cherkasov, Anton V.; Fukin, Georgy K.; Trifonov, Alexander A.; Larionova, Joulia
Abstract : We report the synthesis and magnetic properties of a series of new organometallic homoleptic complexes Li(DME)3 [Ln(DAD)2 ] (Ln = Dy (1a, 1b ), Tb(2 ), and Er(3 )). Abstract : Here, we report the synthesis and magnetic properties investigation of a series of new organometallic homoleptic complexes Li(DME)3 [Ln(DAD)2 ] (Ln = Dy (1a, 1b ), Tb(2 ), and Er(3 )) based on paramagnetic Ln(iii ) ions coordinated by an ene-diamido[2, 6-iPr2 C6 H3 N–CHCH–NC6 H3 iPr2 -2, 6] 2− (DAD) ligand. Dy-based compounds exhibit a genuine single-molecule magnet (SMM) behaviour, while the Tb 3+ analogue shows a field-induced slow relaxation of the magnetisation.